Reports of cases in the Supreme Court of Appeals of Virginia - Leigh, Benjamin Watkins, 1781-1849; Robinson, Conway, 1805-1884; Grattan, Peachy R. (Peachy Ridgway), 1801-1881; Matthews, James M. (James Muscoe), b. 1822; Hansbrough, George W.; Burks, Martin P. (Martin Parks), 1851-1928
Some vols. also contain reports of cases in the General Court of Virginia.